Terson sign: from the eponym to emergency neurosurgery – a review (Jornal Memorial da Medicina, 2020)
Terson's sign (TS) is classically defined as vitreous hemorrhage associated with subarachnoid hemorrhage of aneurysmal origin, being an important predictor of severity, indicating greater morbidity and mortality when compared to patients without the sign. The objective of this study is to review the relationship of Terson syndrome/Terson sign with the prognosis of aneurysmal subarachnoid hemorrhage. A search for original articles, research and case reports was performed on the PubMed, Scielo, Cochrane and ScienceDirect platform, with the following descriptors: Terson sign and subarachnoid hemorrhage. Retrospective, prospective articles and case reports published in the last 5 years and which were in accordance with the established objective and inclusion criteria were selected. Ten (10) articles were selected, in which the available results show an unfavorable prognostic relationship of TS and subarachnoid hemorrhage, because these patients had a worse clinical status assessed on the Glasgow scales ≤ 8, Hunt & Hess > III, Fisher > 3, in addition to intracranial hypertension and location of the aneurysm in the anterior communicating artery complex. The early recognition of this condition described by Albert Terson in 1900 brought an important contribution to neurosurgery, being recognized until nowadays.